Adventureland Di Pekanbaru Dengan Pendekatan Ekologi Arsitektur - Andri Anggesi; Pedia Aldy; Ratna Amanati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The development of town nowadays is not considering humanity side and social relation to the people. pekanbaru with the increasing density of people and also a hectic activities make people get bored and stress easily. Meanwhile pekanbaru has no suitable recreational facilities caused by governor's inability to make tourist attraction. hence, people need to have a place for entertainment and relaxation to eliminate fatigue. adventureland is a place for tour which is full of game and emphasizes to storyline and thinking ability in analyzing a place visually or concluding the things. Design approach applied is more prioritizing the principle of architecture ecology than ken yeang's, with the aim that the designed area has more integrity in the effort of noticing the circumstance around. the design of this area uses